Transmuted Cosine Topp-Leone G Family Of Distributions: Properties And Applications - Osi, Abdulhameed Ado; DOGUWA, SANI; Yahaya, Abubakar; Zakari, Yahaya; USMAN, ABUBAKAR (My University, 2024)
A new trigonometric generalized family of distribution, the "Transmuted Cosine Topp-Leone G Family" is proposed in this study. Established on the foundations of, this family combines the adaptability of the Topp-Leone distribution with the periodicity of the cosine function and transmutation theory to produce a flexible framework that may be used to represent a wide range of real-life phenomena. We derive some of the statistical properties of the introduced family such as; survival and hazard functions, and moment and moment-generating function. Moreover, the model parameters are estimated using the Maximum Likelihood method, and a Monte Carlo simulation was performed to ascertain the behavior and the consistency of the estimates. Lastly, we demonstrate the applicability of the family on the two-lifetime datasets.
Keywords: Tope Leone G; Cosine-G; Transmuted-G